Zadania gminy w zakresie zbiorowego zaopatrzenia w wodę i zbiorowego odprowadzania ścieków - Kaźmierska-Patrzyczna, Aneta (Acta Universitatis Lodziensis. Folia Iuridica, 2009)
In accordance with the European Union law, the Polish legislator has transferred the tasks of communal water supply and communal channeling of sewage to the citizen’s closest local government of district rank. What lies in the heart of these tasks is rendering services within the scope of consumption, treatment and delivery of water or channeling and purifying sewage by water and sewer authority. These are the local government’s own tasks as their aim is current and ceaseless process of satisfying collective needs of the local community. This means that the district carries out duties of this type always in its own name and on its own responsibility even in a situation when these are not performed by the local authority itself since it is mainly the private sector which renders such services for the district. On this account, the role of district authorities in the area of communal water supply and communal sewage channeling involves providing proper and effective performance of duties which were imposed on the district as part of direct execution tasks (organization tasks), regulatory and rationing tasks as well as control and supervision tasks.